La gobernabilidad de la cooperación internacional para el desarroallo de México - Prado Lallande, Juan Pablo (Revista Española de Desarrollo y Cooperación, 2023)
During the last decades Mexico has been driven by different routes (not always linear) in order to foster better governance on its international cooperation for development (ICD) activities. The recent Mexican ICD Act, complementary to the existing acquis in this regard, will contribute to improve a State policy in this stratgic area of Mexican foreign policy. This article analyzes the scope and limits of governance of Mexican IDC on the frame of the entry into force of the latter Law.